“A Slippery Slope of Nakedness:” An Exploration of Online Nude Content Exchange by Gay and Bisexual Men - Restieri, Andrew Lawrence (AoIR Selected Papers of Internet Research, 2026)
High-profile cases of gay influencer nude leaks have prompted widespread discussions of the risks and harms of how gay and bisexual men who exchange intimate content online negotiate privacy, risk, and sexual desire. Indeed, gay and bisexual men who use geosocial dating apps like Grindr are significantly more likely to be the victims of revenge porn than both the general population and the gay community more broadly. Yet, the critique imagines intimacy, exposure, hurt, and harm through histories of heterosexual desire. This project will engage in a queering of discourse around sexting and revenge porn through a qualitative interrogation of four areas of practice: taking, sharing, disseminating, and consuming nude and pornographic content. In doing so, this research will contribute to new ways of thinking sexting and revenge porn that are unburdened by heteronormative expectations and hegemonic constraints on online sexual expression.